Angiopoietin-like 4 regulates epidermal differentiation - Mintu Pal (2011)
The nuclear hormone receptor PPARβ/δ is integral to efficient wound re-epithelialization and implicated in epidermal maturation. However, the mechanism underlying the latter process of epidermal differentiation remains unclear. We showed that ligand-activated PPARβ/δ indirectly stimulated keratinocyte differentiation, requiring de novo gene transcription and protein translation. Using organotypic skin cultures constructed from PPARβ/δ- and angiopoietin-like 4 (ANGPTL4)-knockdown human keratinocytes, we showed that the expression of ANGPTL4, a PPARβ/δ target gene, is essential for the receptor mediated epidermal differentiation. The pro-differentiation effect of PPARβ/δ agonist GW501516 was also abolished when keratinocytes were co-treated with PPARβ/δ antagonist GSK0660 and similarly in organotypic skin culture incubated with blocking ANGPTL4 monoclonal antibody targeted against the C-terminal fibrinogen-like domain. Our focused real-time PCR gene expression analysis comparing the skin biopsies from wildtype and ANGPTL4-knockout mice confirmed a consistent down-regulation of numerous genes involved in epidermal differentiation and proliferation in the ANGPTL4-knockout skin. We further showed that the deficiency of ANGPTL4 in human keratinocytes and mice skin have diminished expression of various protein kinase C isotypes and phosphorylated transcriptional factor activator protein-1, which are well-established for their roles in keratinocyte differentiation. Chromatin immunoprecipitation confirmed that ANGPTL4 stimulated the activation and binding of JUNB and c-JUN to the promoter region of human involucrin and transglutaminase type 1 genes, respectively. Taken together, we showed that PPARβ/δ regulates epidermal maturation via ANGPTL4-mediated signalling pathway.